2009
DOI: 10.4021/jocmr2009.03.1226
|View full text |Cite
|
Sign up to set email alerts
|

Carotid Atherosclerosis in Ischemic Cerebrovascular Patients

Abstract: BackgroundCerebral emboli resulting from atherosclerosis at the carotid bifurcation is a major cause of ischemic stroke. A convenient and prompt evaluation is necessary for secondary prevention and treatment.MethodsIn this study, one hundred and thirty eight patients with cerebral ischemic events were enrolled; 100 patients with nonischemic cerebral diseases were enrolled as controls. Noninvasive ultrasound was used to measure the atherosclerotic plaques and intima-media thickness (IMT) of carotid and femoral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…21 Carotid atherosclerosis can reflect cerebral atherosclerosis to some extent and is an important predictor of cerebral infarction. 22 The previous study 23 confirmed that the incidence of severe and unstable carotid atherosclerosis was higher in patients with ischemic stroke. Hyperhomocysteinemia is an independent risk factor for carotid atherosclerosis and is significantly related to the degree of carotid atherosclerosis.…”
Section: Effect Of Hyperhomocysteinemia On Carotid Atherosclerosis (Imentioning
confidence: 70%
“…21 Carotid atherosclerosis can reflect cerebral atherosclerosis to some extent and is an important predictor of cerebral infarction. 22 The previous study 23 confirmed that the incidence of severe and unstable carotid atherosclerosis was higher in patients with ischemic stroke. Hyperhomocysteinemia is an independent risk factor for carotid atherosclerosis and is significantly related to the degree of carotid atherosclerosis.…”
Section: Effect Of Hyperhomocysteinemia On Carotid Atherosclerosis (Imentioning
confidence: 70%
“…Carotid atherosclerosis plaque is significant in the formation of cerebral infarction. 49 , 50 Research has proven that a slight progression of carotid atherosclerosis significantly and positively increases the prevalence of cardiovascular disease and the risk of future cardiovascular disease events. 51 , 52 Moreover, intima-media thickness of the carotid arteries is a marker of atherosclerosis, as has been assessed pathologically.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of embolic cerebral infarction in patients with unstable CAP was higher than in those with stable CAP. Unstable CAP is significant in the formation of cerebral infarction (1315). Patients with severe carotid stenosis or intracranial vascular stenosis were excluded from the current study.…”
Section: Discussionmentioning
confidence: 99%